Assessment of nutrition and nutritional status in women using the high–protein diet in the past - Reguła, Julita; Jurczak, Roksana; Wyka, Joanna; Baczynska, Sandra (Progress in Nutrition, 2018)
Background. High-protein diets are often used as a quick and easy way to achieve weight loss in those who are overweight or obese. People using for a long time this type of diet are not aware that it can cause serious health problems, therefore it is very important to monitor the effects of long-term use of high-protein diets. Aim. The aim of this study was to evaluate the high–protein diet (Dukan Diet) and after its completion, as well as to assess the nutritional status of women on the basis of biochemical parameters of blood: morphology, blood sugar, lipid profile and hepatic profile, in order to determine the health consequences of the high-protein diet. Material and Methods. The study included 32 women aged 19 to 56, who had followed the Dukan Diet in the past (2 year ago). A 7-day nutrition diary was used to assess nutrition after the Dukan Diet, where 5 days were working days and 2 days were non-working days. Nutritional status was assessed on the basis of anthropometric measurements and the morphological and biochemical parameters of blood: blood count, fasting blood glucose levels, lipid profile, the profile of the hepatic were analyzed in an accredited analytical laboratory, and these values were determined using  haematological and biochemical indicators measured on an Analyzer at Sysmex K-1000 and Vitalab Flexor, respectively. Results. The resulting analysis shows that women did not receive adequate amounts of energy from the diets. Diets were deficient in terms of most nutrients, while in other cases the values exceeded the recommended standards. Analysis has shown that the Dukan Diet is deficient in many vitamins, including vitamins C and B, nor does this diet provide a sufficient amount of dietary fiber. It has been observed of minerals deficiency (iron, magnesium, copper) both during and after the protein diet. Moreover, subjects revealed an increased concentration of eosinophils, basophils, monocytes, triglycerides, LDL cholesterol, glucose in the blood. Conclusions. The diet of women after the end of high-protein diet is still abnormal as evidenced by improper blood chemistry markers. Women should be under the control of a dietitian.